2017
DOI: 10.1002/ptr.5868
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Ischemic Brain Edema by Combined use of Paeoniflorin and Astragaloside IV via Down‐Regulating Connexin 43

Abstract: Paeoniflorin (PF) and astragaloside IV (AS-IV) have protective effects on cerebral ischemia. We aimed to test the effects of combined use of PF and AS-IV on ischemic brain edema and investigate whether the effects were dependent on connexin43 (Cx43). We detected the expression of Cx43 induced by PF and AS-IV after cerebral ischemia. We also examined the effects of combined use of PF and AS-IV on ischemic edema and further investigated the related pathways. We demonstrated PF and AS-IV decreased Cx43 and aquapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Paeoniflorin (PF; Figure a) is a major pharmacologically active ingredient derived from Paeonia lactiflora Pall, which has been widely applied in traditional Chinese medicine to treat various diseases for centuries (Arentz et al, ; Parker et al, ). Recent years, PF has been confirmed to exhibit anti‐inflammatory, antiviral, antibacterial, antioxidant, antinociceptive, and immunoregulatory therapeutic activity (Chu et al, ; Xu, Xu, & Deng, ). An increasing number of evidences report that PF can improve cholestasis (Z. Chen et al, ), hepatitis (M. Chen et al, ), non‐alcoholic fatty liver disease (Ma et al, ), and hepatic I/R injury (Tao, Wen, Song, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Paeoniflorin (PF; Figure a) is a major pharmacologically active ingredient derived from Paeonia lactiflora Pall, which has been widely applied in traditional Chinese medicine to treat various diseases for centuries (Arentz et al, ; Parker et al, ). Recent years, PF has been confirmed to exhibit anti‐inflammatory, antiviral, antibacterial, antioxidant, antinociceptive, and immunoregulatory therapeutic activity (Chu et al, ; Xu, Xu, & Deng, ). An increasing number of evidences report that PF can improve cholestasis (Z. Chen et al, ), hepatitis (M. Chen et al, ), non‐alcoholic fatty liver disease (Ma et al, ), and hepatic I/R injury (Tao, Wen, Song, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pathophysiologically, astrocytic Cx43 has been connected to ischemic stroke [ 42 , 43 ], to the formation of brain edema, for instance after ischemia or trauma [ 44 , 45 ], to cancers of diverse tissues (reviewed by [ 46 ]), or to the response to mechanical stress [ 47 ], making the regulation and functionality of Cx43 subject of many studies [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combined use of paeoniflorin and astragaloside IV was shown to reduce the incidence of ischemic brain edema via the downregulation of connexin 43, which was associated with downregulation of Cx43, resulting in a decrease in AQP4 [22]. The results obtained in the present study have also shown that AQP4 is the key link in the glial lymphatic system, a new clearance system in the brain which was identified in the rodent brain in 2012, and considered as a new anatomical route for CSF-interstitial fluid flow [23].…”
Section: Discussionmentioning
confidence: 99%